Les dynamiques sociales engendrées par l’implantation du parc éolien le Nordais - Étienne Lyrette; Michel Trépanier (VertigO)
The socials dynamics generated by the implantation of Le Nordais windmills farm-The implantation of a windmills farm in a rural and low-density area can generate some opposition from the citizens who are directly affected by the project (Not In My Back Yard syndrome - NIMBY -). The analysis of the implantation of this type of infrastructure must be done according to criterias that go beyond the environmental benefits of wind energy or the small number of opponents to the project.